Safety of calcidiol monohydrate produced by chemical synthesis as a novel food pursuant to Regulation (EU) 2015/2283. (1st July 2021) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Peláez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of calcidiol monohydrate as a novel food (NF) pursuant to Regulation (EU) 2015/2283, including its bioavailability as a metabolite of vitamin D3 when added for nutritional purposes to food supplements. The NF is produced chemically. It is proposed in food supplements up to 10 μg/day for individuals ≥ 11 years of age, including pregnant and lactating women and up to 5 μg/day in 3‐ to 10‐year‐old children. The production process, composition, specifications and stability of the NF do not raise safety concerns. Animal and human data indicate efficient absorption. The NF contains a fraction of nanoparticles, which are fat soluble and unlikely to reach systemic distribution. There are no concerns regarding genotoxicity. Human adult studies do not raise safety concerns. Combined intake estimates of calcidiol from the NF and calcidiol and vitamin D from the diet were below the tolerable upper intake level (UL) for vitamin D for subjects above 11 years of age. The achieved mean serum 25(OH)D concentration in adults supplemented with 10 μg NF per day remained below 200 nmol/L. The Panel concludes that the NF is safe under the proposed conditions of use and use levels for individuals ≥ 11 years old, including pregnant and lactating women. The applicant did not provide data on the bioavailability and safety of the NF in children. The combined intake estimation in children (3–10 years) is close to the UL for vitamin D. Therefore, the Panel could not conclude on the safety of consumption of the NF in children (3–10 years) at the proposed daily intake. The NF is a bioavailable source of the biologically active metabolite of vitamin D, i.e. 1, 25‐dihydroxyvitamin D.